Environmental and Economic Prospect Analysis in the Development of the Blue Economy in Patutrejo Village (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The blue economy has the principle of sustainable management in various sectors between the ocean and the coast. The blue economy emphasizes economic growth and frames the sea and coast as a space for development. This research aims to identify and analyze key variables in environmental and economic aspects in the development of the blue economy in Patutrejo Village, Purworejo Regency. This research uses a mix method approach to achieve research objectives with interviews and analysis using ISM (Interpretive Structural Modeling). The results of this research show that there are three blue economy sectors, including aquaculture, beach tourism and commodity processing. The research results indicate that water conservation and increasing opportunities for the tourism industry are key variables for developing the blue economy